The effectiveness of using effective microorganisms (EM) in fish market wastewater - Nur Afiza, Ishak (2010)
The increasing pollution of water systems in recent years has been noted that the amount of pollution produced by humans is far exceeds the cleaning capacity of nature. The objectives of the study are to determine the effectiveness of using Effective Microorganisms (EM) in improving the wastewater at the fish market area and to determine the wastewater quality at the fish market area by using EM according to standard from DOE-WQI. The study was conducted at the fish market area which is to determine the wastewater quality before and after adding the Effective Microorganisms (EM). The wastewater quality is determined by done the test according to the parameter of pH, temperature, Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solid (TSS), Ammonia Nitrogen (AN), and Dissolved Oxygen (DO). The parameters are based on the Water Quality Index (WQI) from the Department of Environment (DOE) and will be referred to Standard Examination of Water. and Wastewater by American Public Health Association (APHA,2002). Analysis of data was performed by using 2-way analysis of variance (2-way ANOVA). The significant ANOVA (P<0.05), studies shown the different in values of the monitored the parameters which indicates the data obtained is accurate. The results of WQI is analyze according to the DOE-WQI standard, by using the J-M2 1 there have an improvement to the wastewater and the status of WQI is change from slightly clean to clean status, 75.74 mgIL to 82.94mg/L. By using the Activa Orange there have an improvement to the wastewater and the status of WQI is change from slightly clean to clean status, 75.74mgfL to 83.15mg/L. Knowing the differences of quality of wastewater at fish market area, before and after using the Effective Microorganism (EM), the Effective Microorganism(EM) can be use as a one of the solution to improve the condition and environment of wastewater quality at fish market area by reducing the pollution.